2020
DOI: 10.1111/jfbc.13424
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic properties of rice and wheat bran—A review

Abstract: A large amount of agricultural wastes is being dumped each year and utilized as animal fodder or biogas production or for compost matter. But if properly processed, the by-products available from them can be used effectively for human consumption which exhibits their more or less lucrative value (Wani, Dar, Gull, & Ariana, 2020). An unprecedented amount of agricultural wastes of almost around 1,000 million tons is produced globally and is getting hiked by 5% annually. The recent trend of its usage has been esc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Wheat bran (WB) and wheat straw are by-products of the wheat flour industry. Although there are reports of some of the functional properties of WB and wheat straw fibre (WSF) ( Neyrinck et al, 2011 , Neyrinck et al, 2018 , Budhwar et al, 2020 , Demuth et al, 2020 ), large quantities are wasted during the milling process. WB contains approximately 16% w/w proteins, 4.4% lipids, and 65% carbohydrates (of which 43% is dietary fibre); some of these proteins and lipids exhibit unique activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat bran (WB) and wheat straw are by-products of the wheat flour industry. Although there are reports of some of the functional properties of WB and wheat straw fibre (WSF) ( Neyrinck et al, 2011 , Neyrinck et al, 2018 , Budhwar et al, 2020 , Demuth et al, 2020 ), large quantities are wasted during the milling process. WB contains approximately 16% w/w proteins, 4.4% lipids, and 65% carbohydrates (of which 43% is dietary fibre); some of these proteins and lipids exhibit unique activities.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, WB dietary fibre has been found to contain not only cellulose but also a unique fibre called arabinoxylan ( Demuth et al, 2020 ). Furthermore, there are many reports of the inhibitory effects of WB and whole-grain flour on obesity, diabetes, and colitis ( Budhwar et al, 2020 , Tieri et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ethyl acetate fraction showed potent inhibition with 62.11% at 50 µg/mL. Through a detailed phytochemical investigation on this active fraction, we isolated and identified eight compounds, including flavone (1) and flavonolignans (2)(3)(4)(5)(6)(7)(8). In this study, we describe the isolation, structural identification, and biological results of these compounds and chemotaxonomy significance.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, improved varieties of wheat have been steadily developed with a focus on the high functionality of wheat, such as colored wheat grains having a broad range of colors from red to purple with greater antioxidant activity [3]. An interest in the health benefits of whole grain or wheat bran obtained by milling has been increasing in recent years, and several studies have been reported that whole grain or bran of wheat is helpful in improving health and preventing various diseases such as diabetes, cancer, and allergies [4][5][6][7][8]. However, there are few reports on the phytochemical and biological study of agro-industrial waste produced after threshing wheat, such as the hull (including spike) and straw.…”
Section: Introductionmentioning
confidence: 99%
“…During the processes of milling, bran is removed and seed devoid of bran is used for the consumption (Jun, Song et al 2012). E. coracana bran is presumed to be less nutritional, used as a fodder for animals (Budhwar, Chakraborty et al 2020). However, bran of other species from Poaceae family such as Oryza sativa (O. sativa) and Sorghum bicolor (S. bicolor) is rich in medicinally important phytochemicals.…”
Section: Introductionmentioning
confidence: 99%